Discovery of a Novel Inhibitor of the Protein Tyrosine Phosphatase Shp2 - Chen, Chuan (Nature Publishing Group, 2015)
Shp2 is a ubiquitously expressed protein tyrosine phosphatase (PTP) related to adult acute myelogenous leukemia and human solid tumors. In this report, we describe identification of a potent Shp2 inhibitor, Fumosorinone (Fumos) from entomogenous fungi, which shows selective inhibition of Shp2 over other tested PTPs. Using a surface plasmon resonance analysis, we further confirmed the physical interaction between Shp2 and Fumos. Fumos inhibits Shp2-dependent activation of the Ras/ERK signal pathway downstream of EGFR, and interrupts EGF-induced Gab1-Shp2 association. As expected, Fumos shows little effects on the Shp2-independent ERK1/2 activation induced by PMA or oncogenic Ras. Furthermore, Fumos down-regulates Src activation, inhibits phosphorylation of Paxillin and prevents tumor cell invasion. These results suggest that Fumos can inhibit Shp2-dependent cell signaling in human cells and has a potential for treatment of Shp2-associated diseases.